Home Ranges and Movements of Arctic Fox (Alopex lagopus) in Western Alaska - Anthony, R. Michael (ARCTIC, 1997)
During the period from 1985 to 1990, radio collars were attached to 61 arctic foxes (Alopex lagopus) in the coastal region of the Yukon-Kuskokwim Delta in western Alaska. Radio tracking using hand-held receivers from aircraft and from fixed towers was conducted to determine daily and seasonal movements of foxes. Intensive radio tracking of 18 foxes from May through July indicated that males used larger areas (x = 10.22±6.18 sq. km) than females (x = 4.57±1.94 sq. km) regardless of breeding status. Generally foxes were relocated near (x = 3.4±2.4 km) their summer home ranges during other seasons of the year. There were no complex social groups of foxes among the marked population. Foxes did not have a definitive preference for any plant community, probably because of the even distribution and abundance of prey throughout all communities. Thirty foxes were relocated repeatedly during a period of at least 10 months, which included the denning season of one year and the breeding season of the next. Of 24 confirmed deaths of collared foxes, 16 were caused by shooting or trapping by local residents and 8 had unidentified causes. Maximum distance moved between relocations was 48.4 km. Males moved farther from initial capture sites in the winter following capture than did females, largely because of greater than 20 km movements by two foxes. There were no seasonal differences in movements between males and females. Au cours de la période allant de 1985 à 1990, des colliers émetteurs ont été posés à 61 renards arctiques (Alopex lagopus) dans la région côtière du delta du Yukon-Kuskokwim dans l'Alaska occidental. On a utilisé le pistage radioélectrique effectué à l'aide de receveurs portatifs, depuis des aéronefs et des tours stationnaires pour déterminer les déplacements quotidiens et saisonniers des renards. Un pistage radioélectrique intensif de 18 renards effectué de mai à fin juillet a révélé que les mâles utilisaient une superficie plus vaste (x = 10,22 ± 6,18 km²) que les femelles (x = 4,57 ± 1,94 km²) ...